Analytical heat conduction model of annular composite fins - Gibbons, Michael; Feng, Chen (My University, 2018)
A two-dimensional analytical heat conduction model of an annular composite fin has been carried out.The composite fins composed of a porous polyethylene core, a square aluminum insert,and metallic zinc coating layers, was fabricated using wire-arc spraying technology. Analytical solutions of temperature distribution, energy dissipation and fin efficiency through the fin sat natural convection condition have been proposed.
The Canadian Society for Mechanical Engineering International Congress 2018
Keywords: Composite fins; Heat conduction; Analytical model; ANALYTICAL MODEL; composite fins; heat conduction